2016
DOI: 10.1038/npp.2016.261
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate and Memory and Attention Adaptation Training for Persistent Cognitive Symptoms after Traumatic Brain Injury: A Randomized, Placebo-Controlled Trial

Abstract: The purpose of this multicenter, prospective, randomized, placebo-controlled study was to evaluate and compare the efficacy of two cognitive rehabilitation interventions (Memory and Attention Adaptation Training (MAAT) and Attention Builders Training (ABT)), with and without pharmacologic enhancement (i.e., with methylphenidate (MPH) or placebo), for treating persistent cognitive problems after traumatic brain injury (TBI). Adults with a history of TBI at least four months prior to study enrollment with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…Ramasubbu and Goodyear (2008) carried out a study in a cohort of stroke patients which involved periodic fMRI scanning with two cognitive tasks during a 3-day course of MPh administration and they found increases in activation in the patient WM networks. McDonald et al (2016) found that TBI patients who received a dose of MPh in conjunction with a neurocognitive rehabilitation programme demonstrated improvements in several cognitive domains including WM. Future TBI studies designed to have a daily dose of MPh, periodic cognitive testing and serial MRI scans would add to the current knowledge of the longer term neural activation patterns and pharmacological action of MPh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramasubbu and Goodyear (2008) carried out a study in a cohort of stroke patients which involved periodic fMRI scanning with two cognitive tasks during a 3-day course of MPh administration and they found increases in activation in the patient WM networks. McDonald et al (2016) found that TBI patients who received a dose of MPh in conjunction with a neurocognitive rehabilitation programme demonstrated improvements in several cognitive domains including WM. Future TBI studies designed to have a daily dose of MPh, periodic cognitive testing and serial MRI scans would add to the current knowledge of the longer term neural activation patterns and pharmacological action of MPh.…”
Section: Discussionmentioning
confidence: 99%
“…They also found an improvement in RTs for this group but only in the WM task. More recently, improvements in WM, episodic memory and attention were demonstrated in a TBI patient population in a study which combined MPh with a structured metacognitive rehabilitation programme (McDonald et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In the search for novel 'pro-cognitive' agents, one 'known' or reference drug for attention-enhancing effects is the psychostimulant, amphetamine. Acutely, amphetamine and other psychostimulants are known to have positive effects on specific neurocognitive measures in both healthy subjects (HS) and in individuals with a variety of disabling brain conditions including, among others, attention-deficit hyperactivity disorder (Rapoport et al, 1980), SZ (Barch, 2010;Barch and Carter, 2005;Goldberg et al, 1991;Pietrzak et al, 2010), and traumatic brain injury (Kim et al, 2006;McDonald et al, 2017). Interestingly, procognitive effects of amphetamine (20 mg, po) were not detected among a large cohort of adult HS using the MATRICS Consensus Cognitive Battery (MCCB), a gold standard for detecting procognitive drug effects (Nuechterlein et al, 2008); however, subgroups characterized by low baseline MCCB scores, higher age, and specific personality dimensions did exhibit amphetamineassociated gains in MCCB performance (Chou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PC levels decrease again to normal levels in fly brains after cocaine removal, or after MPH treatment. In addition to ADHD patients, cognitive enhancement following MPH has also been reported for patients with traumatic brain injury as well as depression after stroke (36)(37)(38). Moreover, Goldstein's group showed that the use of a low dose of MPH improved cognitive tasks in cocaine abusers (39).…”
Section: Discussionmentioning
confidence: 95%